(untitled) (Global Journal of Management and Business Research, 1970)
Small and medium-sized enterprises SMEs in Zimbabwe are regarded as the most resilient and the backbone of the economy following years of capital flight since 2000 following the consummation of the fast tract land reform programme Since then major corporates disinvested and this created a huge gap in the products and services supply chain and the SMEs robustly emerged largely owned by the local people This paper however has established that in as much as the SMEs have a critical role to play government aided financing infrastructure is characterised by a plethora of policy and regulatory frameworks that limit growth and development of the SMEs to contribute significantly to the development of the economy Using a review process as a methodology as part of an ongoing doctoral research in this field the paper puts across that it is vitally important for Zimbabwe to put incentives from a policy and tax rebate point of view including lessening the bureaucratic red-tape and rigidities that characterise SMEs loan application to access to capital The various independent and dependent variables in this paper require an overhaul to ensure that the challenges that limit SMEs access to financing are addressed